Infrared-to-visible upconversion: spontaneous emission and amplified spontaneous emission in a ZBLAN:Er3+ optical fiber - Kaczmarek, Franciszek; Karolczak, Jerzy (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
Careful, intensity and spectral examinations of fluorescence in the process of infrared-to-visible upconversion, observed perpendicularly to the excited ZBLAN:Er3+ optical fiber (side fluorescence), and at the fiber end, point to the existence of amplified spontaneous emission (ASE), when the fiber is long enough. We have observed the narrowing of the fluorescence band centered at 544 nm (4S3/2 -> 4I15/2 transition) and an increase in the ASE intensity, when the fiber is pumped at 809 nm with a laser diode.
Optica Applicata, Vol. 37, 2007, nr 1-2, s. 101-106
Keywords: optyka; infrared-to-visible upconversion; amplified spontaneous emission